SPE International Conference and Exhibition on Health, Safety, Security, Environment, and Social Responsibility 2018
DOI: 10.2118/190545-ms
|View full text |Cite
|
Sign up to set email alerts
|

Industry Safety Data, What is it Telling Us?

Abstract: The International Association of Oil & Gas Producers (IOGP) is a global forum in which member companies identify and share best practices to achieve improvements in areas such as health, safety, the environment, security, social responsibility and operations. IOGP members encompass oil and gas companies, industry associations as well as major upstream service companies; collectively members produce 40% of the world's oil and gas. The IOGP member companies voluntarily report their annual safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Wingate et al 9 found that approximately half of transportation fatalities in the OGE industry identified through a pilot study of the Texas Department of Transportation Crash Records Information System were not wearing seat belts. An in-depth study of motor vehicle crash data collected from members of the International Association of Oil & Gas Producers for the year 2015 revealed that most of those fatally injured were not wearing seat belts 36 . New and innovative solutions may be needed to address the ongoing issue of transportation incidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wingate et al 9 found that approximately half of transportation fatalities in the OGE industry identified through a pilot study of the Texas Department of Transportation Crash Records Information System were not wearing seat belts. An in-depth study of motor vehicle crash data collected from members of the International Association of Oil & Gas Producers for the year 2015 revealed that most of those fatally injured were not wearing seat belts 36 . New and innovative solutions may be needed to address the ongoing issue of transportation incidents.…”
Section: Discussionmentioning
confidence: 99%
“…An indepth study of motor vehicle crash data collected from members of the International Association of Oil & Gas Producers for the year 2015 revealed that most of those fatally injured were not wearing seat belts. 36 New and innovative solutions may be needed to address the ongoing issue of transportation incidents.…”
Section: Claims Caused By Transportation Incidentsmentioning
confidence: 99%